2009
DOI: 10.1021/ef800894m
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Effect of CO2Flooding on Asphaltenic Oil Recovery and Reservoir Wettability

Abstract: Miscible and immiscible flooding with CO2 of oils containing asphaltene for chalk reservoir is investigated. Oil recovery from model oil and crude oil (30° API gravity), containing 0.35 and 10 wt % asphlatene, respectively, is addressed. n-Decane is used as a reference oil and showed an increase of recovery from 81 to 89% at 50 °C and 90 bar and 80 °C and 140 bar, respectively. Both model and crude oils showed a reduction in the oil recovery from 78.92 to 70.4% and from 37.6 to 36.6%, respectively, at the same… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
28
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 38 publications
2
28
0
Order By: Relevance
“…In the past five decades, there have been extensive laboratory studies, numerical simulations, and field applications of CO 2 EOR processes [1,[3][4][5][6]. The mechanisms affecting the displacement of oil by CO 2 injection include oil swelling, IFT (interfacial tension), and viscosity reduction as well as increasing the injectivity index due to solubility of CO 2 in water and subsequent reaction of carbonic acid with the minerals [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…In the past five decades, there have been extensive laboratory studies, numerical simulations, and field applications of CO 2 EOR processes [1,[3][4][5][6]. The mechanisms affecting the displacement of oil by CO 2 injection include oil swelling, IFT (interfacial tension), and viscosity reduction as well as increasing the injectivity index due to solubility of CO 2 in water and subsequent reaction of carbonic acid with the minerals [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Hamouda et al (2009) reported higher oil recovery due to better sweep efficiency in cores with higher deposited asphaltene. Among proposed models, none of them can predict asphaltene precipitation which could results to divergence of CO 2 streamlines and higher sweep efficiency.…”
Section: Introductionmentioning
confidence: 97%
“…They have shown that at specific pressure and for specific live oil, CO 2 addition increases the asphaltene stability less than the crossover temperature, while above this point, the asphaltene is more unstable when the CO 2 concentration is increased. Hamouda et al (2009) derived a modified solubility equation to take to account the effect of dissolved CO 2 fraction on asphaltene precipitation. The model considers the volume occupied by one mole of CO 2 and fluid as a function of the solubility parameter of the fluid.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical investigations on the application of CO 2 for EOR started in the early 20th century (Rogers and Grigg, 2000). Over the past few decades, extensive laboratory studies, numerical simulations, and field applications of CO 2 -EOR processes have been reported (Burke et al, 1990;Grigg and Schecter, 1993;Idem and Ibrahim, 2002;Moritis, 2006;Chukwudeme and Hamouda, 2009;Hamouda et al, 2009;Manrique et al, 2010;Enick and Olsen, 2012). Several CO 2 -EOR methods have been suggested and developed, such as continuous CO 2 flooding and Water-Alternating-CO 2 (CO 2 -WAG) flooding under immiscible and miscible displacements.…”
Section: Introductionmentioning
confidence: 99%